Stand Up to Excite the Spine: Neuromuscular, Autonomic, and Cardiometabolic Responses During Motor Imagery in Standing vs. Sitting Posture; Frontiers in Physiology; Vol. 12 - Grospretre S. Sidney; Marusic U. Uros; Gimenez Ph. Philippe; Ennequin G. Gael; Mourot L. Laurent; Isacco L. Laurie (2021, 2021)
Title screen